2017
DOI: 10.1007/s11845-017-1580-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of candesartan on pentraxin-3 plasma levels as marker of endothelial dysfunction in patients with essential arterial hypertension

Abstract: Candesartan decreases PTX3 and hs-CRP plasma levels more powerful than other classes of antihypertensive drugs (beta blockers, calcium channel blockers, and diuretics), so we may assume that candesartan has a more potent action in reversing endothelial dysfunction and that it offers a higher vascular protection than other classes of antihypertensive drugs. We are suggesting that this new biochemical marker, PTX3, might be better and more specific marker for endothelial dysfunction, than hs-CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Only ACEIs increased the vascular response of the forearm to reactive hyperemia by increasing NO production in these patients with essential hypertension. Buda et al [60] demonstrated in a cross-sectional study that treatment with candesartan was associated with lower plasma levels of pentraxin-3 (PTX3) and CRP compared to other classes of antihypertensive drugs (β-blockers, calcium channel blocker, and diuretics) in 365 patients with essential hypertension. On the other hand, Vidal et al [61] showed in a prospective population-based study conducted in Switzerland that the use of ARB was not associated with reduced levels of inflammatory markers when compared with non-users (users of other classes of antihypertensive drugs).…”
Section: Antihypertensive Drugs Endothelial Dysfunction and Inflmentioning
confidence: 99%
“…Only ACEIs increased the vascular response of the forearm to reactive hyperemia by increasing NO production in these patients with essential hypertension. Buda et al [60] demonstrated in a cross-sectional study that treatment with candesartan was associated with lower plasma levels of pentraxin-3 (PTX3) and CRP compared to other classes of antihypertensive drugs (β-blockers, calcium channel blocker, and diuretics) in 365 patients with essential hypertension. On the other hand, Vidal et al [61] showed in a prospective population-based study conducted in Switzerland that the use of ARB was not associated with reduced levels of inflammatory markers when compared with non-users (users of other classes of antihypertensive drugs).…”
Section: Antihypertensive Drugs Endothelial Dysfunction and Inflmentioning
confidence: 99%
“…Even if in the case of pharmaceuticals, the term "stability" is usually correlated with the loss of the active pharmaceutical ingredient from formulation, and "solid-state stability" can also designate the response of an API or a pharmaceutical formulation to thermal stress. However, in both cases, the decomposition of the API due to chemical processes or even physical transitions (phase transitions such as polymorphism and crystallization) in the presence of excipients dictates Acting in a dose-dependent manner, candesartan can be used in several pathologies such as essential arterial hypertension [5], ventricular hypertrophy [6], heart failure [7], diabetic nephropathy, [8] retinopathy [9], myocardial infarction [10], endothelial dysfunction [6,11], prehypertension [12], the prevention of atrial fibrillation [13], migraine prophylaxis [14], and stroke [15]. Recently, it has been shown to ameliorate brain inflammation associated with Alzheimer's disease [16] and to induce neuroprotective effects in patients suffering from Parkinson's disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma PTX3 concentration is reportedly normalized by cardiovascular drugs, including antihypertensive 23–27 , antilipemic 28 , and antithrombotic 29 agents. Although the drug screening test detected the antithrombotic drug warfarin in two cases (case Nos.…”
Section: Resultsmentioning
confidence: 99%